(untitled) (ModaPalavra e-periódico, 2012)
The present paper proposes a reflection through bibliographic search and observation of fast fashion stores about the characteristics of fast fashion market model particularly as regard to the elements used in the creative process of fast fashion companies. There was a considerable loss in the time for search for the creation of a "new thing" due the reduction of space between creation and final product, since the fast fashions prioritize profit over an identity brand with style. In this context, it is up to the consumer to rethink their consumption habits and charge a most ethical stance as regards the quality and demand.